Semiotic analysis of moral messages in the film Women from Rote Island for Christian religious education - Wahju Astjarjo Rini; Seli A. Tagu Sunga; Gracia Paramitha; Novi K. Tahalele; Yonatan Alex Arifianto (Technium Social Sciences Journal, 2025)
This study is entitled Semiotic Analysis of Moral Messages in the Film Woman From Rote Island for Christian Religious Education. The story in the film is taken from the cultural background in East Nusa Tenggara, where women are often victims of domestic violence. This study aims to understand how the moral message in the film is conveyed so that the message can support the values ​​of Christian Religious Education. This film depicts the relationship between humans and others, the relationship between humans and God, and the relationship between humans and the social environment. This study uses a qualitative method, with a Roland Barthes semiotic analysis approach, taking the subject focused on the figure of Orpa representing the image of women in East Nusa Tenggara. Viewed from the Denotation (signifier) ​​aspect, it explains the relationship between the signifier and the signified in reality, producing explicit meaning. Connotation (signified) describes the relationship between the signifier and the signified in non-reality, producing implicit meaning and Myths or customs and beliefs that apply in society. In this study, the scene is focused on the life of Orpa, a woman on Rote Island, East Nusa Tenggara, who experiences violence and discrimination. This discrimination is rooted in centuries-old traditions that stigmatize women as second-class gender in society. In addition to the figure of Orpa, this film will also provide a perspective from Martha, Orpa’s daughter. Martha is one of the women who experienced sexual violence that made her feel depressed and depressed—data collection by determining the corpus contained in the film according to the predetermined categorization. The results of this study indicate that the moral messages contained in the film Women From Rote Island are: First, the importance of upholding the value of resilience in facing difficulties, as described by the character Orpa, who is a single parent raising children. Second, courage and independence in rejecting gender discrimination and violence that occurs in Rote, East Nusa Tenggara. Third, there is concern and compassion for women who are victims of violence, including sexual violence. Moral messages can be seen through the data found in the study so that these three values ​​are then integrated into Christian religious education.